2021
DOI: 10.3390/healthcare9020140
|View full text |Cite
|
Sign up to set email alerts
|

What Do We Know about Early Management of Sepsis and Septic Shock in Polish Hospitals? A Questionnaire Study

Abstract: Background: Sepsis and septic shock are medical emergencies with a high risk of poor prognosis. We investigate the correspondence between Surviving Sepsis Campaign (SSC) guidelines and clinical practice in Poland, with special attention given to differences between ICU and non-ICU environments as well as regional variations within the country. Methods: A web-based questionnaire study was performed on a random sample of 60 hospitals from the three most populated regions in Poland—Masovia, Silesia, and Greater P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Studies Open access in non-paediatric settings have reported moderate-togood levels of practice, 18 although suboptimal practices have been identified regarding the measurement of lactate levels, interval for antimicrobial therapy after a presumptive sepsis diagnosis, use of crystalloids for fluid resuscitation and indications for blood culture. 19 Additionally, there is evidence of insufficient compliance with sepsis guidelines in hospitals in Poland 22 and China. 23 The observed variance between moderate knowledge of sepsis and positive attitudes, alongside proficient practices, may stem from various factors.…”
Section: Discussionmentioning
confidence: 99%
“…Studies Open access in non-paediatric settings have reported moderate-togood levels of practice, 18 although suboptimal practices have been identified regarding the measurement of lactate levels, interval for antimicrobial therapy after a presumptive sepsis diagnosis, use of crystalloids for fluid resuscitation and indications for blood culture. 19 Additionally, there is evidence of insufficient compliance with sepsis guidelines in hospitals in Poland 22 and China. 23 The observed variance between moderate knowledge of sepsis and positive attitudes, alongside proficient practices, may stem from various factors.…”
Section: Discussionmentioning
confidence: 99%